Invariant NKT Cells as Novel Targets for Immunotherapy in Solid Tumors. (17th October 2012) - Pilones, Karsten A.; Aryankalayil, Joseph; Demaria, Sandra
Abstract : Natural killer T (NKT) cells are a small population of lymphocytes that possess characteristics of both innate and adaptive immune cells. They are uniquely poised to respond rapidly to infection and inflammation and produce cytokines that critically shape the ensuing adaptive cellular response. Therefore, they represent promising therapeutic targets. In cancer, NKT cells are attributed a role in immunosurveillance. NKT cells also act as potent activators of antitumor immunity when stimulated with a synthetic agonist in experimental models. However, in some settings, NKT cells seem to act as suppressors and regulators of antitumor immunity. Here we briefly review current data supporting these paradoxical roles of NKT cells and their regulation. Increased understanding of the signals that determine the function of NKT cells in cancer will be essential to improve current strategies for NKT-cell-based immunotherapeutic approaches.